2012
DOI: 10.1371/journal.pone.0045179
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Satiation and Increased Feeding Behaviour in the Triple-Transgenic Alzheimer's Disease Mouse Model

Abstract: Alzheimer's disease (AD) is associated with non-cognitive symptoms such as changes in feeding behaviour that are often characterised by an increase in appetite. Increased food intake is observed in several mouse models of AD including the triple transgenic (3×TgAD) mouse, but the mechanisms underlying this hyperphagia are unknown. We therefore examined feeding behaviour in 3×TgAD mice and tested their sensitivity to exogenous and endogenous satiety factors by assessing food intake and activation of key brain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 64 publications
4
20
0
Order By: Relevance
“…Deregulated hypothalamic functions were reported in AD patients [18]. Consistently, impaired hypothalamic functions such as alternate feeding behaviors and excess food intake are reported in two AD transgenic mice models, 3xTgAD and Tg2576 mice [19,20]. 3xTgAD mice consume more food and are insensitive to cholecystokinin, a potent satiety factor [19].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Deregulated hypothalamic functions were reported in AD patients [18]. Consistently, impaired hypothalamic functions such as alternate feeding behaviors and excess food intake are reported in two AD transgenic mice models, 3xTgAD and Tg2576 mice [19,20]. 3xTgAD mice consume more food and are insensitive to cholecystokinin, a potent satiety factor [19].…”
Section: Introductionmentioning
confidence: 85%
“…Consistently, impaired hypothalamic functions such as alternate feeding behaviors and excess food intake are reported in two AD transgenic mice models, 3xTgAD and Tg2576 mice [19,20]. 3xTgAD mice consume more food and are insensitive to cholecystokinin, a potent satiety factor [19]. Prior to the presence of the amyloid pathology in the hypothalamus, increased food intake and decreased proopiomelanocortin and neuropeptide Y neurons of 3xTgAD mice are observed [21].…”
Section: Introductionmentioning
confidence: 92%
“…Additionally, genetic deletion of Tau resulted in increased body weight [152]. Impaired satiation and increased feeding behavior [153], as well as changes in body temperature [154] were also observed in a mouse model combining amyloid plaques and Tau pathology (3xTgAD). In Tg4510 mice, weight loss was specific to fat mass and co-occurred with deregulation of metabolic rate [151] as well as disturbances in circadian rhythm [98].…”
Section: Brain Insulin Resistance In Ad and Tauopathies: Cause Or Conmentioning
confidence: 99%
“…There are also reports showing physiologic changes in the 3xTg-AD mice evidenced by increased food consumption, changes in weight, increased oxygen consumption, carbon dioxide production, defective gutbrain signaling, changes in core body temperature; thus, showing physiologic hyperactivity. [37][38][39] In addition to the association of hypermetabolism with plaques, a metabolic study in the tau transgenic mouse model of AD showed hypermetabolism in cerebral cortex. 19 Concluding Remarks The major finding of this study is the hypermetabolic state in the 7-month-old 3xTg-AD mice as compared with age-matched nonTg mice and these results are in contrast to the hypometabolism observed in 13-month-old 3xTg-AD mice.…”
Section: Effect Of Lipoic Acidmentioning
confidence: 99%